A notch methodology to estimate fretting fatigue strength - Martins, Luiz Homero Lopes (2007)
The aim of this work is to propose a methodology to estimate the fatigue limit of cylindrical contacts under a partial slip regime. Taylors point stress method, usually applied to estimate fatigue limit for notched structures, was associated with the Modified Wöhler Curves to define the fretting crack initiation thres hold methodology. Twenty-nine tests on cylindrical contacts were selected from the literature and considered to evaluate the quality of the estimates. The results agree well for twenty-three experimental data. As the fatigue limit under fully reversed bending is the fatigue parameter usually available for most metallic alloys, it was also showed how the second fatigue limit needed to calibrate the proposed procedure could be estimated by taking full advantage from other standard predictive methodologies previously devised to estimate the mean stress effect under uniaxial fatigue loading.